The Influence of Educational Institutions on Early Modern Development in Suburban Tokyo, Japan : For the Jesuit School Establishment Project - Genda, Yuta; Nagano, Masayoshi; Nakajima, Naoto (International Planning History Society Proceedings, 2024)
The first modern suburban development in Tokyo, Japan, is Shinmachi Residential Area in Sakura-shinmachi (1913). However, development in the same period was limited and increased in the 1920s. The background of the early development of Shinmachi Residential Area, etc., is still unclear. Therefore, this study aims to clarify the details and characteristics of this area’s modern urban planning history, thereby contributing to the inheritance of a favorable regional environment formed in the modern era. After the Jesuits began selecting lands to establish a school in Japan in 1908, there was a movement to consolidate larger lands in more suburban areas. Specifically, these were Komazawa Village and Kichijoji Village. Finally, Jesuit schools did not come there and were established in Yotsuya, Central Tokyo, as Sophia University. Later, the land in Komazawa Village was developed as Shinmachi Residential Area, and the land in Kichijoji Village was developed as a school town by Seikei Gakuen educational institution, as pioneers in suburban development. Thus, the Jesuit’s international educational involvement partially characterized early modern suburban development in the Tokyo area.